Alpha-Adrenergic Mechanisms in the Cardiovascular Hyperreactivity to Norepinephrine-Infusion in Essential Hypertension - Walther, Lisa-Marie; von Känel, Roland; Heimgartner, Nadja; Zuccarella-Hackl, Claudia; Stirnimann, Guido; Wirtz, Petra H. (Frontiers in Endocrinology, 2022)
Aims Essential hypertension (EHT) is characterized by cardiovascular hyperreactivity to stress but underlying mechanism are not fully understood. Here, we investigated the role of α-adrenergic receptors (α-AR) in the cardiovascular reactivity to a norepinephrine (NE)-stress reactivity-mimicking NE-infusion in essential hypertensive individuals (HT) as compared to normotensive individuals (NT). Methods 24 male HT and 24 male NT participated in three experimental trials on three separate days with a 1-min infusion followed by a 15-min infusion. Trials varied in infusion-substances: placebo saline (Sal)-infusions (trial-1:Sal+Sal), NE-infusion without (trial-2:Sal+NE) or with non-selective α-AR blockade by phentolamine (PHE) (trial-3:PHE+NE). NE-infusion dosage (5µg/ml/min) and duration were chosen to mimic duration and physiological effects of NE-release in reaction to established stress induction protocols. We repeatedly measured systolic (SBP) and diastolic blood pressure (DBP) as well as heart rate before, during, and after infusions. Results SBP and DBP reactivity to the three infusion-trials differed between HT and NT (p’s≤.014). HT exhibited greater BP reactivity to NE-infusion alone compared to NT (trial-2-vs-trial-1: p’s≤.033). Group differences in DBP reactivity to NE disappeared with prior PHE blockade (trial-3: p=.26), while SBP reactivity differences remained (trial-3: p=.016). Heart rate reactivity to infusion-trials did not differ between HT and NT (p=.73). Conclusion Our findings suggest a mediating role of α-AR in DBP hyperreactivity to NE-infusion in EHT. However, in SBP hyperreactivity to NE-infusion in EHT, the functioning of α-AR seems impaired suggesting that the SBP hyperreactivity in hypertension is not mediated by α-AR.